1997
DOI: 10.1128/mcb.17.2.906
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Truncations of the Yeast Nucleoporin Nup145p Produce a Rapid Temperature-Conditional mRNA Export Defect and Alterations to Nuclear Structure

Abstract: A screen for temperature-sensitive mutants of Saccharomyces cerevisiae defective in nucleocytoplasmic trafficking of poly(A)؉ RNA has identified an allele of the NUP145 gene, which encodes an essential nucleoporin. ؉ RNA and fragmentation of the nucleolus occurred rapidly following a shift to 37؇C. Constitutive defects in nuclear pore complex distribution and nuclear structure were also seen in these strains. Although cells lacking Nup145p grew extremely slowly at 23؇C and did not grow at 30؇C, efficient growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Such a phenotype has previously been reported for other individual mRNA export-deficient strains (Kadowaki et al 1994b;Dockendorff et al 1997;Rout et al 2000), and we therefore decided to examine this in general by conducting Nop1p staining of all 15 deletion mutants subjected to a 42°C heat shock for 20 or 40 min. In the more severe cases (e.g., the Dmft1, Drip1, and Dsac3 strains), Nop1p fragmentation was evident in a fraction of the cells already at the 20-min time point and in all cells after 40 min of incubation at 42°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such a phenotype has previously been reported for other individual mRNA export-deficient strains (Kadowaki et al 1994b;Dockendorff et al 1997;Rout et al 2000), and we therefore decided to examine this in general by conducting Nop1p staining of all 15 deletion mutants subjected to a 42°C heat shock for 20 or 40 min. In the more severe cases (e.g., the Dmft1, Drip1, and Dsac3 strains), Nop1p fragmentation was evident in a fraction of the cells already at the 20-min time point and in all cells after 40 min of incubation at 42°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteolytic cleavage of a 186-kD precursor protein yields both Nup96 and Nup98 (Fontoura et al, 1999). The yeast Nup96 homolog, C-Nup145p, is also produced through proteolytic cleavage of a precursor protein that yields both C-Nup145p and N-Nup145p, the Nup98 equivalent in yeast (Dockendorff et al, 1997;Emtage et al, 1997;Teixeira et al, 1997). Database searches revealed that MOS3 is the only Nup96 homolog and the message for MOS3 only encodes AtNup96.…”
Section: Es4326 Growth Of Psm Es4326 In Mos3-1 and Mos3-2 Ismentioning
confidence: 99%
“…When detected by in situ hybridization using oligo dT probes, minimal poly(A) + signal is present within the nucleus. In screening for nuclear poly(A) + RNA retention using temperature-sensitive mutants as well as single gene deletion strains, initial studies identified many genes involved in mRNA export (Gorsch et al 1995;Heath et al 1995;Li et al 1995;Saavedra et al 1996;Dockendorff et al 1997). For the essential genes identified by nuclear poly(A) + retention, the lethal phenotype was thought to be caused by a general defect of mRNA export.…”
Section: Introductionmentioning
confidence: 99%